Automatic key holder - Noor Azahan, Nur Alya Syahirah; Mohd Termidzi, Nik Nurfatihah; Setapa, Mariam; Safie, Shafiza; Mustafa, Tismazammi; Rahman, Khairunnisa; Ab Rahman, Siti Maziah (Universiti Teknologi MARA, Perak, 2023)
In the world today, various types of innovations are seen to have benefited the world so much for a better future. It is crucial for an innovation to be aligned with the context and level of development within a country especially for developing countries such as Malaysia. Up to 90% of people in developing countries own traditional key and lock systems and many of those are unable to manage the physical key bunch effectively. The importance of effective key organizations could avoid potential issues thus providing better security and affordable costs. An analysis is done on the statistics of poverty and the capability of households in absorbing the surging living cost obtained from the Department of Statistics Malaysia (DOSM) and the Congress of Unions of Employees in the Public and Civil Services (CUEPACS). From the observation, the transition from the use of traditional key and lock systems to the use of smart access door systems might be too much for the developing country. This study of effective key management has led to the innovation of the automatic key holder which is realistic with the development of the developing country, as well as improving individual efficiency. The automatic key holder is innovated from the manual key organizer with the adoption of the current automatic car key concept. This simple yet meaningful innovation is an effective solution for key management in developing countries.